P082 OCULAR EVALUATIONS IN INFLAMMATORY BOWEL DISEASE: STEROID USE AND PATIENT ETHNICITY INFLUENCE REFERRAL RATES. (18th January 2018) - Dave, Jenny; Almedimigh, Abdulaziz; Alsulaimi, Najwan; Fairfield, Bradley; Myint, Aung; Borum, Marie L
Abstract: Approximately 4–10% of individuals with inflammatory bowel disease (IBD) will have ocular manifestations. In addition, steroid use is associated with ophthalmologic complications. Annual ophthalmology evaluations are recommended for all IBD patients. However, it is uncertain if IBD patients are consistently referred for eye examinations. This study evaluated the frequency of ophthalmology referrals in IBD patients and the rate of eye disease. A record review of all IBD patients seen at an university gastroenterology practice during a 6 month period was performed. Patient age, gender, ethnicity, disease type (Crohn's', ulcerative colitis) and ophthalmology referrals were obtained. A database was created maintaining patient confidentiality. Analysis was conducted using Fisher's Exact Test with significance set at p<0.05. The study was approved by the university IRB. Records of 268 patients (118 men, 150 women; mean age 43; 158 Crohn's disease, 109 ulcerative colitis, 1 indeterminate) were reviewed. 160 (70%) patients were referred to an ophthalmologist. Whites were referred (77/143; 53.85%) more frequently (p=0.015) than nonwhites (67 of 96; 69.79%). There was a difference in the rate (p=0.001) at which patients with prior steroid use (94/138; 68.12%) and steroid-naïve patients (62/130; 47.69%) were referred. 39 (15.67%) patients had documented eye disease, with no difference (p=0.480) between patients with prior steroid use (10/138) and steroid naïve patients (19/102). Ophthalmology evaluations are an important component of IBD management. In this study, 60% of all IBD patients were referred to an ophthalmologist, with white patients referred more frequently than non-whites and steroid users referred more frequently than steroid naïve patients. While this study is limited by size and single institutional design, it emphasizes the need to consistently refer IBD patients for ophthalmology evaluations. Efforts to decrease referral disparities are necessary.